Association Between Lipid Profile and The Clinical Course of Influenza - Lagadinou, Maria; Polyzou, Eleni; Michailides, Christos; Amerali, Marina; Marlafeka, Ioanna; Leonidou, Leonidia; Chartoumpekis, Dionysios; Marangos, Markos (Archives of Clinical and Medical Case Reports, 2025)
Background: Influenza remains a major cause of morbidity and mortality worldwide. Identifying biomarkers associated with disease severity could improve risk stratification and patient management. Aim: The aim of this study was to investigate the association between lipid profile and the clinical outcomes of influenza infection, especially among adults who were either admitted to the hospital or were treated as outpatients after being diagnosed with influenza in the emergency department (ED). Results: The median age of the total cohort was 59.9 ± 20.7 years, with 47.8% being male and 52.2% female. Patients in the hospitalized group were significantly older than those managed as outpatients (70.2 ± 15.6 vs 40.1 ± 23.1 years, p=0.002). Among all lipid parameters, only Low-Density Lipoprotein (LDL) levels were significantly lower in hospitalized patients compared to outpatients (76.6 ± 30.3 vs 98.4 ± 22.6 mg/dL, p=0.038). To assess the impact of treatment, lipid values measured upon admission were compared with those recorded after clinical recovery. No significant changes were detected in any lipid marker, including Total Cholesterol (TC), LDL, High-Density Lipoprotein (HDL), and Triglycerides (TG), indicating that the treatment course did not substantially alter lipid levels. No significant correlations were identified between White Blood Count (WBC) and TC, HDL, LDL, or TG, with Pearson correlation coefficients ranging from -0.08 to 0.17. When lipid levels were analyzed in relation to patient age, TG demonstrated a weak positive correlation with age (r=+0.08). Triglycerides were the best severity predictor (AUC=0.87), followed by C-Reactive Protein (CRP) (AUC=0.85). A comparison between the influenza cohort and 32 healthy control subjects revealed significantly lower levels of TC, HDL, and LDL among patients with influenza (all p < 0.001 for TC and LDL, and p=0.002 for HDL). Triglyceride levels did not differ significantly between the two groups (p=0.681). Conclusion: LDL shows a consistent inverse correlation with hospitalization and age. Triglycerides have high discriminatory ability for severe influenza infection. These findings highlight the potential role of lipid profile -particularly LDL and TG—as indicators of disease severity and proliferated immune response in influenza infection. The observed differences warrant further investigation in larger and more diverse patient populations.